The artist and her biographical secrets. A few thoughts about a student of prominent woodcut artist – Stanislaw Ostoia-Chrostowski’s - Maciąg, Paweł W. (Biografie nieoczywiste: Przełom, kryzys, transgresja w perspektywie interdyscyplinarnej, 2018)
The author of the text presents an intriguing biography of the artist Maria Hiszpańska-Neumann. He analyses in detail the education stages of the painter, from her childhood to studies at the Academy of Fine Arts in Warsaw, providing rich documentation on the subject as the source material. The author recounts the painter’s traumatic experiences during her imprisonment in the Ravensbruck and Neubrandenburg camps. He stresses that, as well as Maria Hiszpańska-Neumann, there was no shortage of Polish talented female artists in the camp. He states that even the cruelty of war could not stop human beings from striving for the beauty of art. In times when the order of human norms was reversed, the accepted norms, moral, ethical and social systems were rejected, and when limitations, penalties and restrictions were introduced, the war did not kill art itself. The author, on the basis of literature as well as the transcript of interviews with Wanda Półtawska, Alicja Gawlikowska and Bogna Neumann, attempts to render a psychological portrait of Maria Hiszpańska-Neumann the most known student of Stanisław Ostoja-Chrostowski.